2009
DOI: 10.2144/000113198
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Temperature-Gated Ion-Channel Activity Using a Real-Time PCR Machine

Abstract: The functional activity of a number of ion channels is highly sensitive to large changes in temperature. Foremost among these are the thermosensing TRP channels which include cold- (TRPM8, TRPA1), warmth- (TRPV3, TRPV4), and heat-sensing (TRPV1, TRPV2) members. TRPV1, also known as the vanilloid receptor (VR1), is activated by ligands such as capsaicin, acidic pH, and heat (an increase in temperature to approximately 42 degrees C will lead to channel opening). Screening against the thermal gating of TRPV1 is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…reported (21). We also developed the RT-PCR heat activation assay (data presented by Papakosta et al at FASEB Ion Channel Conference, June, 2009) but we found that our FLIPR heat activation assay was far superior in terms of assay window and reproducibility in a high-throughput format.…”
Section: Development and Validation Of Flipr Heat Activation Assaymentioning
confidence: 88%
“…reported (21). We also developed the RT-PCR heat activation assay (data presented by Papakosta et al at FASEB Ion Channel Conference, June, 2009) but we found that our FLIPR heat activation assay was far superior in terms of assay window and reproducibility in a high-throughput format.…”
Section: Development and Validation Of Flipr Heat Activation Assaymentioning
confidence: 88%
“…To functionally characterize the effects of the mammothspecific N647D substitution, we resurrected the AncMammoth and AncGajah TRPV3 genes and measured their temperaturedependent gating in transiently transfected HEK293 cells using Fluo-4 calcium flux assays (Aneiros and Dabrowski, 2009;Reubish et al, 2009). We found that both the AncMammoth and AncGajah TRPV3 proteins were expressed at similar levels (Figure S5I) and that the overall gating dynamics of channels were very similar.…”
Section: Substitutions In Temperature-sensitive Transient Receptor Pomentioning
confidence: 95%
“…Temperature-dependent calcium influx was assayed using the Fluo-4 NW Calcium Assay Kit (Molecular Probes) and a high-throughout qPCR-based assay (Aneiros and Dabrowski, 2009;Reubish et al, 2009). After an initial 30-min loading at 25 C, the temperature was raised from 15 C to 57 C in 2 C steps, and fluorescence was measured after 2 min at each temperature using a Bio-Rad CFX-96 real-time PCR machine.…”
Section: Trpv3 Function Assaysmentioning
confidence: 99%
“…To functionally characterize the effects of the mammoth-specific N647D substitution we resurrected the AncMammoth and AncGajah TRPV3 genes and measured their temperature-dependent gating in transiently transfected human embryonic kidney cells (HEK293) using Fluo-4 calcium flux assays Reubish et al, 2009). We found that both the AncMammoth and AncGajah TRPV3 proteins were expressed at similar levels (SI Fig.…”
Section: Thermal Tuning Of the Woolly Mammoth Temperature Sensor Trpv3mentioning
confidence: 99%